PENGARUH PEMBERIAN RAGI DAN TEPUNG JAMUR TIRAM (PLEUROTUS OSTREATUS) DALAM PROSES PEMBUATAN TEMPE KEDELAI TERHADAP KANDUNGAN LEMAK DAN TEKSTUR SEBAGAI BAHAN AJAR KELAS XII SMA - diah ayu febriani; Endah Rita Sulistya Dewi; Ipah Budi Minarti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT Tempeh, as a fermented soybean product, has the potential to be developed through innovation using natural additives to improve its nutritional quality and texture. This study aims to determine the effect of adding yeast and oyster mushroom flour (Pleurotus ostreatus) on the fat content and texture of soybean tempeh, as well as to implement the research results as teaching materials in the form of Student Worksheets (LKPD) for Biotechnology learning in grade XII senior high school. This research is an experimental study with three treatments, namely without yeast (P0), addition of yeast (P1), and addition of yeast and oyster mushroom flour (P2). Each treatment was repeated three times. The obtained data were analyzed using ANOVA and followed by Duncan’s test to determine differences among treatments. The results showed that the treatments had a significant effect on both fat content and texture of soybean tempeh. The P2 treatment (yeast and oyster mushroom flour) produced the lowest fat content and the softest tempeh texture compared to other treatments. The ANOVA test results indicated that the calculated F value was higher than the F table value at a 5% significance level for both fat content and texture, meaning that the hypothesis was accepted. In addition, the developed LKPD was categorized as valid to highly valid based on expert validation, indicating that it is suitable for use in Biotechnology learning. This study contributes to the development of tempeh-based fermented food products and produces contextual teaching materials that can enhance students’ understanding of biotechnology concepts. Keywords: tempeh, yeast, oyster mushroom, fermentation, fat content, texture, LKPD, biotechnology.